Product development in custom-made medical devices - Ramos, Victor Quintana (2021)
The 21st century presents a revolution in additive manufacturing, and these technologies will continue to grow. Osteobionix S.L., the company where the internship took place, has been designing and producing titanium prosthetic parts for human implantation since 2008. The company’s goal is to design and build parts of the human body tailored for patients in which standard prostheses do not solve the problem. Based on this, the company’s methodology was to obtain 3D images of each case, discuss, design and build a final solution. As soon as the solution is accepted by the surgeon, it proceeds to the production phase, mainly using an electron beam fusion machine (ARCAM S12). The objective in the internship time was to understand the company’s workflow, help in the production line and develop some design cases in order to learn and analyze what is a complete design follow-up case. The main results obtained are the prototypes that are manufactured in EBM. Licensing for human use and implantation of products in humans is a slow process. Animal testing should be the next step to obtain useful data. Finally, several cases developed during the internship will be presented and explained.